The Notion of Self-Access Language Learning in Malaysia - Andrew, Yau-hau Tse (2013)
Just a few Malaysian universities offer self-access language learning activities to students. The objective of this study is to investigate if self-access learning can promote self-directed or autonomous learning in a public Malaysian technical university. Data collection is by means of interviewing the Director, lecturers, and students in a self-access language learning centre (SALLEC). The findings revealed students find it helpful and useful to exploit the self-learning materials in the centre. Lecturers strongly agree that the centre can promote autonomous learning. To conclude, self-learning should be promoted in Malaysia to enhance language learning and acquisition.